In Tamil Nadu... Exploring gladiolus through cyber extension - Pravin, T Raj; Nazir, Manoj (Indian Horticulture, 2019)
Tamil Nadu is blessed with 13 coastal districts involved in the cultivation of horticultural crops catering to the needs of mainland areas. The successful introduction of gladiolus and its marketing in metropolitan cities and in nearly foreign geographics will pave way for prosperity among small and marginal farm community belonging to poor socio-economic status and disadavantaged groups, thereby making colour revloution in Tamil Nadu, a reality in progress in the near future. Extension efforts and policy initatives of central and state government in strengthening this extension efforts will bring about inclusive growth in backward regions of Tamil Nadu, improving the floricultural contribution to the national economy.